Effects of Separate and Combined Chronic Ingestion of Codeine and Tramadol on Feeding Behaviour of Female Albino Rats. - Balogun, S.K.; Osuh, J.I.; Onibokun, O.O. (Jour Med Resh and Health Sci, 2020)
Tramadol and codeine are both opioids used for pain control and management but are prone to misuse and abuse despite the various side effects. This study, therefore, examined the effects of chronic exposure to Codeine and Tramadol on feeding behaviour. Twenty-Four (24) Female Albino Rats weighing between 150-200g and 4-6 weeks old, were used. They were divided into 4 experimental groups of Codeine, Tramadol, combined Codeine and Tramadol and Control groups with 6 rats in each group and exposed to 8mg/kg of codeine, 20mg/kg of tramadol, combined 8mg/kg of codeine and 20mg/kg of tramadol, and normal saline for 28 days. Records of the amount of food ingested and the bodyweight of the rats were taken daily for the duration of the experiment. Randomized block ANOVA showed a significant effect of Codeine and Tramadol on feeding behavior (F (3,641) = 25.53, p < 0.001, ?2= .11), and body weight (F (3,641) = 76.67, p < 0.001, ?2= .26), among the female rats. Female rats in the combined codeine and tramadol group ingested less food (x ?=33.45), compared to codeine group alone (x ?=40.71), tramadol group alone (x ?=39.96) and control group (x ?=49.38). Female rats in the combined codeine and tramadol group gained less weight (x ?=132.67), compared to codeine group alone (x ?=137.67), tramadol group alone (x ?=133.33), and control group (x ?=164.25). The mean differences were significant (p<.001). It was concluded that chronic exposure to tramadol and codeine has effects on feeding behaviour and subsequent body weight.